[Is the prevalence of rheumatoid arthritis truly on the rise?] - Albrecht, K.; Callhoff, J.; Strangfeld, A. (Z Rheumatol, 2022)
A growing number of health insurance data analyses show an increase in the prevalence of rheumatoid arthritis (RA) in Germany. The studies refer to the claims diagnosis of RA, which is more frequent in recent years compared to earlier periods. Depending on the case definition, the numbers vary between 0.6% and 1.4% of the adult population. In this paper, the different studies are reviewed with regard to their data sources, the case definitions of RA and the frequency of the diagnosis. Due to the lack of clinical validation, the prevalence cannot be precisely determined from claims data.